2017
DOI: 10.1016/j.cell.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Genome Organization Drives Chromosome Fragility

Abstract: SUMMARY In this study, we show that evolutionarily conserved chromosome loop anchors bound by CTCF and cohesin are vulnerable to DNA double strand breaks (DSBs) mediated by topoisomerase 2B (TOP2B). Polymorphisms in the genome that redistribute CTCF/cohesin occupancy rewire DNA cleavage sites to novel loop anchors. While transcription- and replication-coupled genomic rearrangements have been well documented, we demonstrate that DSBs formed at loop anchors are largely transcription-, replication-, and cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
432
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(478 citation statements)
references
References 70 publications
44
432
1
1
Order By: Relevance
“…DSB sites were still predicted well (AUROC = 0.869 and AUPR = 0.792; Additional file 1: Figure S5a and S5b), and CTCF and H3K4me1 were the most highly predictive variables (Additional file 1: Figure S5c). This revealed enhancer looping as a major driver of DSBs, in agreement with recent studies showing that DSBs form at loop anchors [35] and that CTCF facilitates DSB repair [36]. These results demonstrate that DSBs can be accurately predicted at less than 1-kb resolution using just a small amount of data.…”
Section: Prediction Using Epigenomic and Chromatin Datasupporting
confidence: 77%
See 3 more Smart Citations
“…DSB sites were still predicted well (AUROC = 0.869 and AUPR = 0.792; Additional file 1: Figure S5a and S5b), and CTCF and H3K4me1 were the most highly predictive variables (Additional file 1: Figure S5c). This revealed enhancer looping as a major driver of DSBs, in agreement with recent studies showing that DSBs form at loop anchors [35] and that CTCF facilitates DSB repair [36]. These results demonstrate that DSBs can be accurately predicted at less than 1-kb resolution using just a small amount of data.…”
Section: Prediction Using Epigenomic and Chromatin Datasupporting
confidence: 77%
“…Based on lasso regression, we found that the CTCF motif had the highest beta coefficient (β = 3.22), corresponding to OR = 25 (Fig. 7c), supporting recent evidence showing that long-range contacts are involved in DNA repair [25,35,41]. Furthermore, motifs of tumor proteins p53, p63, and p73 had high coefficients (β > 2.03, OR > 7.6), in agreement with previous predictions based on To assess the significance of those motifs, we built a logistic regression model without any regularization including all motifs with β > 0.5.…”
Section: Prediction From Dna Motifs and Shapementioning
confidence: 52%
See 2 more Smart Citations
“…In addition to TDP2-related functions, ZNF451 displays TDP2-independent effects on the cellular response to TOP2 poisoning that will require further investigation. It will be important in future work to elucidate the mechanics of ZNF451-TDP2 influence on TOP2 and its potential for modulating TOP2 regulation of genome dynamics and transcription (4, 12, 31, 32). Given ZNF451 association with TDP2- mediated TOP2 repair, we propose renaming it to ZATT ( Z inc finger protein A ssociated with T DP2 and T OP2) to appropriately reflect these cellular functions.…”
mentioning
confidence: 99%